Chinese Medicine Formula PSORI-CM02 Alleviates Psoriatic Dermatitis via M-MDSCs and Th17 Crosstalk - Deng, Jingwen; Tan, Siyi; Liu, Ruonan; Yu, Wanlin; Chen, Haiming; Tang, Nan; Han, Ling; Lu, Chuanjian (Frontiers in Pharmacology, 2021)
Psoriasis is a chronic inflammatory skin disease that is associated with multiple coexisting conditions. Extensive literature suggests that psoriasis is a T-cell-mediated condition, and its pathogenesis is related to dysfunction of the immune system. Myeloid-derived suppressor cells (MDSCs) are a group of heterogeneous myeloid cells that have suppressive effects on T cells. MDSCs are present at very low levels in healthy individuals but can substantially expand in tumours or inflammatory conditions. PSORI-CM02, a Chinese medical formula designed based on the Chinese medicine theory (Blood Stasis), has been prescribed extensively for psoriasis therapy and shows a stable clinical effect and safety. This study discusses the mechanisms of MDSCs involved in disease development and therapeutic progress. Our data provides evidence that monocytic myeloid-derived suppressor cells (M-MDSCs) play a role in IMQ-induced psoriatic dermatitis. Functional characterization and correlation analysis indicated that MDSCs are positively correlated with Th17 cells. PSORI-CM02 alleviated IMQ-induced psoriatic dermatitis and suppressed the proliferation of Th17 cells via M-MDSC-induced Arg1 upregulation, suggesting M-MDSCs could be a novel therapeutic target for psoriasis, and PSORI-CM02 exerted its effects via the perturbation of M-MDSCs and Th17 cell crosstalk.